Lung Cancer Associated With Cystic Airspaces. Issue 1 (January 2015) - Mascalchi, Mario; Attinà, Domenico; Bertelli, Elena; Falchini, Massimo; Vella, Alessandra; Pegna, Andrea Lopes; Ambrosini, Valentina; Zompatori, Maurizio
<x xml:space="preserve">Abstract</x> Objective This study aimed to define computed tomographic morphologic features of lung cancer associated with cystic airspaces, their modifications in serial computed tomographic scans, and 18F-fluoro-2-deoxy-D-glucose (FDG) positron emission tomography uptake. Methods Computed tomographic scans and 18F-FDG positron emission tomography in 24 patients with lung cancer (17 adenocarcinomas, 7 squamous cell carcinomas, 12 stage I and 12 stage II to IV) associated with cystic airspaces were reviewed. Results Mean diameter of airspace was initially 17.6 mm (range, 5–30 mm), and 4 morphologic patterns were recognized: solid nodule protruding externally (type I, n = 5) or internally (type II, n = 4) from the cyst wall; circumferential thickening of the cyst wall (type III, n = 8); and tissue intermixed within clusters of cysts (type IV, n = 7). With tumor growth, airspace size decreased in 9, increased in 6, and was unchanged in 9 cases. Five cases evolved from type III to type I, and 5 lesions became completely solid. 18F-fluoro-2-deoxy-D-glucose uptake was initially absent to mild in 7 and moderate to marked in 14 lesions. Conclusions Progressive wall thickening or appearance/increase of a nodule inside or outside a cystic airspace should raise suspicion of lung cancer irrespective of FDG uptake.